Evidence for reduced immune gene diversity and activity during the evolution of termites. Issue 1945 (17th February 2021) - He, Shulin; Sieksmeyer, Thorben; Che, Yanli; Mora, M. Alejandra Esparza; Stiblik, Petr; Banasiak, Ronald; Harrison, Mark C.; Šobotník, Jan; Wang, Zongqing; Johnston, Paul R.; McMahon, Dino P.
Abstract : The evolution of biological complexity is associated with the emergence of bespoke immune systems that maintain and protect organism integrity. Unlike the well-studied immune systems of cells and individuals, little is known about the origins of immunity during the transition to eusociality, a major evolutionary transition comparable to the evolution of multicellular organisms from single-celled ancestors. We aimed to tackle this by characterizing the immune gene repertoire of 18 cockroach and termite species, spanning the spectrum of solitary, subsocial and eusocial lifestyles. We find that key transitions in termite sociality are correlated with immune gene family contractions. In cross-species comparisons of immune gene expression, we find evidence for a caste-specific social defence system in termites, which appears to operate at the expense of individual immune protection. Our study indicates that a major transition in organismal complexity may have entailed a fundamental reshaping of the immune system optimized for group over individual defence.